Possible Challenges in The Implementation of the Disability Policy under the Ministry of Community Development and the Department of Social Services in Lusaka Zambia (British Journal of Multidisciplinary and Advanced Studies, 2025)
The purpose of the study was to establish possible challenges in the implementation of the disability policy under the ministry of community development and the department of social services. The study used qualitative approach and adopted phenomenological research design. The sample for the study was 10 people with disabilities, 3 headteachers, 2 community development officers and 2 social welfare officers making the total sample of 17 participants. Data was collected using focus group discussion with people living with disabilities. The discussions were in three sessions because they were three in each session and the last session had four participants and data was analysed using thematic analysis. The study found that the challenges which were faced included lack of policy implementation due to lack of funding from stakeholders. It was also found that the lack of special units in the main stream schools brought about exclusion of the children with disabilities because they cannot have equal access to education as other children. Therefore, the intra policy disagreements made the departments of different ministries dealing with people living with disabilities to work in isolation instead of coordinating activities. The lack of professional training for other government employees are enshrined in the policy documents which tend not to have disability disaggregated data for the whole country. The study recommended that the universities and other professional institutions should ensure that they include a component of handling people with disabilities in their training packages so that they can make every profession to be aligned with the disability inclusion policy. This will enable all professional training for other government and public employees be inclusive.